Diversity and Species Composition of Sponges (Porifera: Demospongiae) in Reef Flat of Barranglompo Island (Torani Journal of Fisheries and Marine Science, 2020)
Sponge is one of the biota that makes up coastal and marine ecosystems, especially in coral reef ecosystems and seagrass beds in both tropical and subtropical waters. The lack of research and knowledge about sponges (Porifera; Demospongiae), especially in the reef flat ecosystem on Barranglompo Island, is considered necessary to be studied and equipped for research on marine biological resources in the future. This research was conducted in March-November 2019 on Barranglompo Island. The purpose of this study was to determine the diversity and species composition and density of sponges (Porifera: Demospongiae) in the reef flat of Barranglompo Island, Sangkarang District, Makassar City. The method used in sponge data collection is a belt transect starting from ± 50m of shoreline drawn perpendicular to the end of the back reef at each station. The diversity of sponge species found was 22 species belonging to the Demospongiae class. The diversity of sponges on Barranglompo Island is still quite diverse, with a fairly even distribution.
Keywords: sponge; species composition; diversity; Barranglompo